Wiley Practitioner's Guide to GAAS 2012 : Covering all SASs, SSAEs, SSARSs, and Interpretations. - Bragg, Steven M. (John Wiley & Sons, 2011)
The clearest, easiest-to-use guide to understanding GAAS 2012 on the market - fully updated. This latest resource to understanding GAAS addresses the toughest part of the job - identifying, interpreting, and applying the many audit, attest, review, and compilation standards relevant to a particular engagement. The only GAAS reference organized according to practitioners' actual use of the Statements on Auditing Standards (SASs), inside you'll find examples and illustrations for testing internal controls, techniques for remaining compliant with each standard, and explanations of the reaso.